Monetary Policy and Financial Performance of Commercial Banks in Uganda: A Case Study Centenary Bank, Kabale Branch. - Kemigisha, Phiona (Kabale University, 2023)
The study examined monetary policy on financial performance of commercial banks in Uganda a case study Centenary bank Kabale branch. The objectives of the study were; to establish the role of monetary policy on the financial performance of the Centenary Bank Kabale branch. to examine the effect of bank size on the performance of the Centenary Bank Kabale branch and to establish the relationship between monetary policy and financial performance. The study used a cross-sectional study and data was collected using interviews and questionnaires. The study findings on the role of monetary policy on the financial performance of commercial banks. the highest number of the respondents mentioned leads to quick and informed decisions while the least number or· the respondents mentioned easy payments of the employees. The study findings on the effect of bank size on the performance of commercial banks, the highest number of respondents mentioned that bank size determines the amount of deposits which improves on the performance of the bank, the lowest number of respondents mentioned that bank size determines the capital ratio used in daily operations which leads to performance of the bank and bank size determines the money supply in operations of bank which leads to performance. The stud) findings on the relationship between monetary policy and financial performance. the highest number of respondents mentioned that monetary policy regulates the supply of money and the lowest number of respondents mentioned that monetary policy leads to stabilization of inflation and promotes the growth of public debt. The study recommended that monetary policy has a significant effect on the financial performance of commercial banks therefore; Centenary bank Kaba le branch should study and incorporate the ever-changing operating environment of the bank when making changes or adjustments in the monetary policies of the bank and the management of the Centenary bank Kabale branch should reduce unnecessary operating costs and ensure it adopts fixed and less costly contracts to reduce on the operation cost levels in the bank. The areas for the study included the effect of monetary policy and the performance of microfinance institutions. the role of managers in managing commercial banks performance and effect of lending policies on bank performance in Uganda.